Making Reading Easier: How Genetic Information Can Help. (October 2017) - Luciano, Michelle
Reading is the cornerstone of all educational systems. Without adequate reading skills, learning in all other subject areas becomes very challenging. Children typically learn basic reading skills by age 6 or 7, but there is variation in timing of reading skill acquisition and, thereafter, in reading ability. A strong predictor of whether a child will have difficulties with reading is family history. Twin and family studies confirm that reading ability (including specific reading disorder) is substantively genetically influenced. Molecular genetic studies of reading ability have identified a number of candidate genes that are associated with reading disability and/or reading processes; many more are likely to be discovered. This review discusses implications that increased understanding of the genetic architecture of reading ability has for early identification and intervention for children at risk for reading difficulties.